Provision of Peanuts as Additional Food in Stunting Prevention for Pregnant Women During the COVID-19 Pandemic: A Systematic Review - Sampeanggin, Henrick; Gandeng, Yulianus; Supriyatno, Heru (Poltekkes Kemenkes Palu, 2024)
During pregnancy, meeting the needs of nutritious food and drinks is very much needed. The development and growth of the fetus including length and weight at birth is an illustration of one of the factors of the mother's nutritional status. To analyze and identify scientific evidence related to peanut as supplementary feeding in preventing stunting babies in pregnant women during the Covid-19 pandemic. This article is a systematic review. The PRISMA diagram was used based on a checklist to determine the articles to be analyzed. PICOT (P: pregnant women, I: peanut, C: -, O: stunting prevention, T: 2017 - 2022) and MESH. The databases used in the search for articles include Willey Online Library, Garuda, ProQuest, Science Direct, Google Scholar, and PubMed. There were 21,937 articles obtained from the search process from the database. There are 5 articles that were reviewed, from the result of the critcal assesment RCT CASP & JBI CASP check list for Quasi-Experimental. In the CASP RCT there are 11 questions, the initial 2 questions about research focus and sampling, if you have 2 answers Yes the article can be used. The JBI Critical Appraisal Checklist contains 9 questions, while the determination of the grade and level of each article uses Johns Hopkins Nursing Evidence-Based Practice. To assess the risk of bias, the authors used the Cochrane Risk Of Bias Assessment Tool which consists of 7 domains. Giving peanuts to pregnant women has a very significant effect in preventing stunting during the Covid-19 pandemic. This is because giving peanuts as additional food to pregnant women and toddlers can increase body weight and upper arm circumference of pregnant women, improve nutritional status, increase protein and energy intake, increase milk production in pregnant women, and increase the duration of pregnancy. The limitations of some articles obtained are some articles do not do blind in on giving treatment to participants, sample size some articles found little sample.